Population status of the Antarctic shag Phalacrocorax (atriceps) bransfieldensis. Issue 3 (30th January 2018) - Schrimpf, Michael; Naveen, Ron; Lynch, Heather J.
Abstract: Antarctic shags Phalacrocorax ( atriceps ) bransfieldensis are the southernmost cormorants in the world and assessment of their conservation status has been complicated by the logistical challenges of obtaining regular estimates of population size, as well as by taxonomic ambiguity of the blue-eyed shag complex. The available information on the taxonomy, distribution and population size of Antarctic shags are reviewed and a refined estimate of the global population is presented: 11 366 breeding pairs, plus an additional 1984 pairs of uncertain taxonomic status in the South Orkney Islands. This analysis suggests a possible spatial shift in the distribution of Antarctic shags similar to that reported for other Antarctic seabirds, which probably reflects a gradient in environmental changes along the western Antarctic Peninsula. This review should aid future conservation and management assessments.